The Path to a Tele-Library Through Knowledge Management Services - Ring, K. (Journal of Information and Knowledge, 1992)
Development of communication facilities helped libraries to give access to people beyond its fourwalls and help delivery of the information at the point of use. This does not, however, obviate the archival function, provision for relaxed and recreative reading, self-education and other activities. Tele-access is one more part of library services in addition to all the other traditional services.